2005
DOI: 10.1108/09654280510595245
|View full text |Cite
|
Sign up to set email alerts
|

The impact of group teaching on the acquisition of key skills to teach personal, social and health education

Abstract: Purpose ? The paper seeks to report the impact of a partnership training intervention on trainee teachers' confidence to teach Personal, Social and Health Education. Design/methodology/approach ? This intervention required trainee teachers to work in 15 groups of four across subject disciplines. Each group was required to negotiate, plan and deliver their intended lesson on PSHE in a partnership school. The initiative was evaluated on a pre- and post-test basis by getting each trainee to complete a PSHE Key Sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(38 citation statements)
references
References 29 publications
(44 reference statements)
0
37
0
1
Order By: Relevance
“…After applying the inclusion criteria described in the previous section to the 31 pre-service publications, 20 studies reported in a total of 21 publications 25,26,44,61,63,70,81,83,92,94,117,142,148,156,174,189,191,195,200,201,213 were included in the synthesis (one study was reported in two separate publications, 26,156 and data from both of these were extracted for this report), with 10 references 57,67,85,88,116,179,192,199,202,206 being excluded. Table 45 provides an overview of the key characteristics of the included studies.…”
Section: Results Of the Synthesismentioning
confidence: 99%
See 4 more Smart Citations
“…After applying the inclusion criteria described in the previous section to the 31 pre-service publications, 20 studies reported in a total of 21 publications 25,26,44,61,63,70,81,83,92,94,117,142,148,156,174,189,191,195,200,201,213 were included in the synthesis (one study was reported in two separate publications, 26,156 and data from both of these were extracted for this report), with 10 references 57,67,85,88,116,179,192,199,202,206 being excluded. Table 45 provides an overview of the key characteristics of the included studies.…”
Section: Results Of the Synthesismentioning
confidence: 99%
“…26,61,63,70,81,83,94,117,148,174,189,191,195,200,213 The comprehensiveness of the information, as reported by the study authors, varied. For example, Chifunyise and colleagues, 81 who provided training to teachers to support the acquired immunodeficiency syndrome (AIDS) and Life Skills Education programme in primary and secondary schools in Zimbabwe, specified that teachers were taught 'basic facts' about transmission, symptoms and prevention of sexually transmitted diseases and human immunodeficiency virus (HIV) infection/AIDS, but no further detail was given (p. 378).…”
Section: Training Contentmentioning
confidence: 99%
See 3 more Smart Citations